Analysis of factors linked to vaccine delay in children: a look at the light of evidence (Research, Society and Development, 2022)
The relevance that vaccines have protection against health and prevention of vaccine-preventable diseases is undoubtedly, especially during childhood. The objective was to discuss, in the light of detection, what are the factors linked to vaccination delay in children. The present study deals with an integrative review, a collection of data that took place in search of the best evidence within the existing literature. A search was performed using a search in the following databases: MEDLINE®, LILACS and BDENF. The inclusion requests used were scientific articles, master's and doctoral dissertations, studies in Portuguese, English and Spanish, full text available electronically and free of charge, published in the last 5 years. Works that do not meet the guiding research question were excluded. Seven articles were selected for analysis of the integrative review, and for the best discussion they were divided into three categories: factors related to sociodemographic aspects, factors related to aspects of UBS statistics and factors related to the performance of the ESF and the health of children who contributed vaccination delay. The authors also reveal that the reduction in vaccination coverage is due to multifactorial causes. Understand that, despite the important findings of this study that subsidizes the management and policies aimed at vaccination coverage, there are some configurations that do not enable the study. Given the above, the evidence and the impact that immunization has on health, it is essential that information and statistics on immunization be shared, such as the development of studies that can collaborate with improvements and the elucidation of other issues related to immunization actions.